Correction: Ingenbleek, L. et al. Regional Sub-Saharan Africa Total Diet Study in Benin, Cameroon, Mali, and Nigeria Reveals the Presence of 164 Mycotoxins and Other Secondary Metabolites in Foods - Luc Ingenbleek; Michael Sulyok; Abimbola Adegboye; Sètondji Epiphane Hossou; Abdoulaye Zié Koné; Awoyinka Dada Oyedele; Chabi Sika K. J. Kisito; Yara Koreissi Dembélé; Sara Eyangoh; Philippe Verger; Jean-Charles Leblanc; Bruno Le Bizec; et al. (Toxins, 2019)
The authors wish to make the following corrections to their paper [...]